Elongation Factor Ts from the Antarctic Eubacterium Pseudoalteromonas haloplanktis TAC 125: Biochemical Characterization and Cloning of the Encoding Gene - RAIMO G; LOMBARDO, BARBARA; MASULLO M; LAMBERTI, ANNALISA; LONGO O; ARCARI, PAOLO (Biochemistry, 2004)
The elongation factor Ts was isolated from the psychrophilic Antarctic eubacterium Pseudoalteromonas haloplanktis TAC 125 strain (PhEF-Ts), and its functional properties were studied. At 0 degrees C PhEF-Ts enhanced the [(3)H]GDP/GDP exchange rate on the preformed PhEF-Tu.[(3)H]GDP complex by 2 orders of magnitude even at very low Tu:Ts ratio, by lowering the energy of activation of the exchange reaction. PhEF-Ts is a monomeric protein, and in solution it forms a stable dimeric complex with PhEF-Tu. The PhEF-Ts encoding gene was cloned and sequenced. Its structural organization was similar to that of Escherichia coli because it showed at its 5' end the gene encoding the ribosomal protein S2. The translated amino acid sequence had a calculated molecular weight of 30762, and showed a high sequence identity with E. coli (68%) and Thermus thermophilus (44%) EF-Ts. The PhEF-Ts primary structure contains well-preserved almost all the amino acid residues interacting at the interfaces of the E. coli EF-Ts.EF-Tu complex. Finally, the high concentration of PhEF-Ts in this psychrophilic eubacterium might represent an adaptive tool to ensure an efficient nucleotide exchange even at low temperature.